REVITALISASI POSISI JAKSA SEBAGAI DOMINUS LITIS DALAM MEWUJUDKAN PERADILAN CEPAT - Gulo, Cornelius Dikae Zolohefona; Rudiyanto, Anton (Penerbit Universitas Atma Jaya Yogyakarta, 2025)
The prosecutor plays a very central role in law enforcement, particularly in criminal law. The law enforcement process cannot be separated from one of the supervisory authorities of the Attorney General, which, according to the principle inherent in his position, is dominus litis. The regulation of the dominus litis principle in criminal procedural law is still not effective; prosecutors only receive case files when the investigation is already complete and are not involved from the beginning of the investigation. This will have significant implications for evidence presentation in court. The purpose of involving prosecutors from the investigation stage is to realize swift justice (constante justitie) and facilitate the prosecutor's task of presenting evidence and to revitalization the position of prosecutor as a dominus litis. When prosecutors and law enforcement officials assume a supervisory role, legal certainty becomes paramount. The methods used are the statute, comparative, and conceptual approaches.